Alterações salivares em ratos após 5/6 nefrectomia: novos biomarcadores salivares para doença renal crônica - Miura, Fernanda Ladico (2017)
Chronic Kidney Disease (CKD) is considered a serious public health problem in Brazil and worldwide and has shown changes in oral health. The present study investigated the effects of CKD on salivary secretion in rats. Wistar rats at 4 weeks of age were used, which were divided into control, sham and CKD groups. After 6 weeks of CKD induction, non-stimulated and pilocarpine-stimulated salivary flow rates were measured in anesthetized rats. After that, salivary glands were removed. Oxidative stress levels, glutathione antioxidant defense system and antioxidant status were analyzed in submandibular glands. The spectroscopy profile and concentrations of alpha-amylase, IgA, cortisol and total proteins of stimulated saliva were analyzed by Fourier transform infrared (FTIR) spectroscopy. Receptor Operation Characteristic Curve (ROC) analysis was performed to determine the diagnostic capacity of each salivary biomarker for CKD. The data demonstrated that body weight remained unchanged in CKD compared to the controls and sham rats. Water consumption, uremia, and kidney weight increased (P<05) in CKD compared to controls and sham rats. Pilocarpine-stimulated salivary flow and salivary glands weights were similar (P<0,05) in DRC, controls and sham rats. Non-stimulated salivary flow was reduced (P<0,05) in CKD than controls and sham rats. CKD increased the oxidative stress levels and the activity of FRAP and GSH in submandibular glands when compared to controls and sham rats. Salivary cortisol concentration was increased in CKD rats than controls and sham rats. Differently, salivary IgA was decreased in CKD condition. Diagnostic potential of salivary cortisol provided sensitivity of 88.9% and specificity of 80% (ROC = 0.911) (P<0,05) and; salivary IgA provided sensitivity of 87.5% and specificity of 100% (ROC = 0.975) (P<0,05). In addition, we have shown that salivary cortisol and IgA measured by FTIR spectroscopy present great potential as biomarkers for chronic renal disease..